Experimental Study and Numerical Simulation Analysis on Reinforcement of Mortise-Tenon Joints with Flat Steel Strips - Shurong Gan; Wen Pan; Hexian Su; Yucheng Jin; Chuanwei Zhu; Shibin Yu (Advances in Civil Engineering)
To study the aseismic performance after the reinforcement of the mortise-tenon joints of folk houses with traditional Chuan-Dou style wood structure and their steel plate, test specimens of joints—two for Tou mortise-tenon joints, two for Ban mortise-tenon joints, and two for dovetail mortise-tenon joints—were fabricated out of hemlock, and steel plates were utilized to reinforce one of the joint specimens of each type on the middle part of the mortise-tenon joint. By carrying out pseudo-static tests on the joints and building ABAQUS numerical model; the position where the mortise-tenon joints were to be reinforced by the steel plates was optimized for a comparative analysis into the test results on reinforced and unreinforced mortise-tenon joints and the numerically simulated bending moment-turning angle hysteresis curve, skeleton curve, energy-dissipating capacity, and rigidity degeneration curves. The results showed the following: the pulling-out phenomenon of tenons was severe, and the aseismic performance of Tou tenons was superior to Ban tenons and dovetail tenons; reinforcing the middle part of mortise-tenon joints with steel plates could effectively reduce the pulling-out amount of joints and promote the aseismic performance of mortise-tenon joints but have an insignificant promotive effect for the bearing capacity of Tou mortise-tenon joints; the aseismic performance was improved significantly after the flat steel strip reinforced position was moved to the upper and lower ends of mortise-tenon joints, with the ultimate bearing capacities being 1.5∼2.4 times that on the middle part of flat steel strip reinforced joints.